On the environmental pollution problem: A review - Oke, Sunday Ayoola (Journal of Environmental Engineering and Landscape Management, 2004)
The commercial sector of most industrialised economy accounts for a significant percentage of the total environmental pollution (EP) that we experience today. Recent advancements in EP research have therefore provided environmental regulators and health scientists with a wide array of solution techniques. Unfortunately, the EP literature has lagged behind in providing an up‐to‐date integrated stream of research that could be useful for new entrants and experienced researchers. The objective of the paper is to present a comprehensive review of EP research. The principal motivating factor is the deficiency of informative articles that reveal the length, breadth and depth of scientific investigations in the area. The study extends to a general survey, models, empirical studies and cases that have extended the frontier of knowledge in EP research. Our aim is to stimulate further empirical and theoretical developments in the EP area. A second intent is to argue that research into EP provides great potentials for increasing our knowledge regarding environmental management. The future holds promising results for researchers and practitioners engaged in EP research. Future studies are expected to save billions of dollars through development of novel cost‐effective methods. Aplinkos užterštumo problemų apžvalga Santrauka. Į aplinkos orą išsiskiriančių teršalų kiekį labai lemia pramonės ekonomika. Tai patvirtina tyrimai aplinkosaugos ir sveikatos mokslų srityse. Darbe siekiama pateikti išsamią apžvalgą šia tematika. Iš esmės informatyvių straipsnių, sukurtų modelių, empirinių tyrimų ir pan. trūksta. Mūsų tikslas ‐ paskatinti bei plėtoti empirinius bei teorinius šios srities tyrimus. Svarbu sutelkti mokslinį potencialą vykdant aplinkosaugini valdymą. Gautieji rezultatai ateityje bus reikalingi kitiems tyrinėtojams ir mokslininkams. Būsimos studijos sutaupys milijonus dolerių plėtojant naujus bei efektyvius aplinkosauginius metodus. Reikšminiai žodžiai: teršalai, vanduo, oras, dirvožemis. First Published Online: 14 Oct 2010